Agent or Borrower? An Incentive of Moral Hazard with China Commercial Guarantee Company. (23rd March 2014) - He, Feng; Zhang, Wei; Zhang, Yongjie; Xiong, Xiong
Abstract : This paper studies the behavior of commercial guarantee company in the game theory framework. Different payoff structures with guarantee company behavior for banks, borrowers, and the guarantors are formed in the presence of credit rationing. We derived and explained the surviving rule of different types of guarantee companies, and we further conclude the condition in which guarantee companies are likely to be involved in a moral hazard problem. We conclude that, in the presence of regulatory arbitrage opportunity, the guarantee company has incentive to switch its role from bank agent to the borrower, being a second-hand lender. When the macroeconomic risk is high, the switching of this role will transfer the risk back to the banks.